Electrical conductivity of a methane–air burning plasma under the action of weak electric fields. (25th January 2017) - Colonna, G; Pietanza, L D; D'Angola, A; Laricchiuta, A; Vita, A Di
Abstract: This paper focuses on the calculation of the electrical conductivity of a methane–air flame in the presence of weak electric fields, solving the Boltzmann equation for free electrons self-consistently coupled with chemical kinetics. The chemical model GRI-Mech 3.0 has been completed with chemi-ionization reactions to model ionization in the absence of fields, and a database of cross sections for electron-impact-induced processes to account for reactions and transitions activated in the flame during discharge. The dependence of plasma properties on the frequency of an oscillating field has been studied under different pressure and gas temperature conditions. Fitting expressions of the electrical conductivity as a function of gas temperature and methane consumption are provided for different operational conditions in the Ansaldo Energia burner.